2008
DOI: 10.1021/bm801065u
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and High Gas Barrier Films of Cellulose Nanofibers Prepared by TEMPO-Mediated Oxidation

Abstract: Softwood and hardwood celluloses were oxidized by 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidation. The TEMPO-oxidized cellulose fibers were converted to transparent dispersions in water, which consisted of individual nanofibers 3-4 nm in width. Films were then prepared from the TEMPO-oxidized cellulose nanofibers (TOCN) and characterized from various aspects. AFM images showed that the TOCN film surface consisted of randomly assembled cellulose nanofibers. The TOCN films prepared from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
771
7
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,161 publications
(814 citation statements)
references
References 18 publications
31
771
7
5
Order By: Relevance
“…Chemical surface modification efficiently tackles this problem (Habibi 2014). Among the many different routes for surface modification reported, esterification with acetic anhydride or long chain carboxylic acids (Rodionova et al 2010;Lee et al 2011;Bulota et al 2012);grafting of polymers (Lönnberg et al 2008;Littunen et al 2011;Missoum et al 2012);cationization (Hasani et al 2008;Syverud et al 2010); silylation (Goussé et al 2004;Andresen et al 2006;Lu et al 2008a, b), and TEMPO oxidation (Saito et al 2006;Fukuzumi et al 2009) are mentioned as important examples. Even though highly successful at the laboratory scale, the up-scaling of these wetchemical approaches to industrial dimensions, involving partly pricey reagents and repeated solvent transfers is most probably quite cost-intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical surface modification efficiently tackles this problem (Habibi 2014). Among the many different routes for surface modification reported, esterification with acetic anhydride or long chain carboxylic acids (Rodionova et al 2010;Lee et al 2011;Bulota et al 2012);grafting of polymers (Lönnberg et al 2008;Littunen et al 2011;Missoum et al 2012);cationization (Hasani et al 2008;Syverud et al 2010); silylation (Goussé et al 2004;Andresen et al 2006;Lu et al 2008a, b), and TEMPO oxidation (Saito et al 2006;Fukuzumi et al 2009) are mentioned as important examples. Even though highly successful at the laboratory scale, the up-scaling of these wetchemical approaches to industrial dimensions, involving partly pricey reagents and repeated solvent transfers is most probably quite cost-intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to thickness development (figure 4), the buckling wavelengths show a linear propagation as well (figure 5a), with an increasing rate for PVAm-SiO 2 -PVAm-NFC than for PVAm-NFC. It has been reported elsewhere [1][2][3][4][5] that the buckling wavelength increases with increasing the number of layers. The Young' modulus, however, should not be affected by thickness over a certain thickness range [9][10][11][12][13] which is also demonstrated here in figure 5b.…”
Section: Resultsmentioning
confidence: 80%
“…It has also been shown that both CNC and NFC can be incorporated into Layer-by-Layer (LbL) self assemblies to yield films with controlled thickness and hence controlled optical properties depending on the composition of the film [3,4]. Recent investigations have also shown that it is possible to prepare freestanding films on NFC [5,6] with controlled barrier properties and with very low oxygen permeabilities at low relative humidities (RH). Another very interesting property of the NFC material is the very good mechanical properties of films and nano-papers prepared from this material [7] and free-standing LbL´s from NFC and Poly EthyleneImine (PEI) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tensile strength and Young's modulus of TEMPO-oxidized cellulose films have been reported to be 200−300 MPa and 6−7 GPa. 67 The EDS spectra showed 1.2 At% Na atomic concentration for CNF film, reflecting the presence of sodium carboxylate on the CNF surfaces, and the Na content increased to 2.0, 2.5, and 2.4 At% for CNF/AgNS, CNF/4AgNP, and CNF/8AgNP, respectively, possibly due to the additional Na absorption from NaBH 4 ( Figure 5c, Table 1 The appearance of all fcc crystal facets in CNF/AgNS confirms its isotropic nature while the low intensity reflects the low quantity of AgNSs. The XRD spectra of all films exhibited clear cellulose I crystalline structure between 10 and 30°same as reported for CNFs alone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%